Analisis faktor konsentrat pakan terhadap konsumsi asam-asam amino ayam ras petelur - Utiah, W.; Paputungan, U. (Universitas Sam Ratulangi, 2021)
ANALYSIS OF FEED CONCENTRATE FACTOR ON LAYING HEN AMINO ACIDS CONSUMPTION. Laying hens require a number of elements in which nutrients such as protein containing the amino acids are balanced in quality. Recently, there are various types of commercial ration (concentrate) for laying hens produced by the company. Quality of protein is expressed either high or low composition of amino acids depending on the essential amino acids contained in these feeds. The purpose of this study was to determine the effect of different types of commercial concentrates on the consumption of amino acids in laying chicken. The research was conducted on laying chicken farms located in Matali Village, district of East Kotamobagu, Kotamobagu Municipality. Laying hens of Silver Strains as many as 240 heads at 78-week-old were used in this study. This study applied a completely randomized design (CRD) consisting of three treatments and eight replications at each treatment. The treatments were using commercial concentrations of the amino acids for commercial Concentrate A (RA), commercial concentrate B (RB) and commercial concentrate C (RC). The laboratory analysis showed that the majority amounts of essential amino acids (Arginine, Lysine, histidine, leucine, isoleucine, valine, threonine and phenylalanine) of 80% was higher in RC than RB and RA, indicating that the composition of both quality and quantity of amino acids in commercial concentrates C (RC) is sufficient and more balanced than commercial concentrates A (RA) and commercial concentrate B (RB). These complete amino acids in RC increased more feed consumption of laying hens compared with those in RA and RB.Key words: Laying hens, amino acids, commercial concentrate